Konten Digital dalam Perkembangan Bahasa Ekspresif Anak Usia Dini: Tinjauan Psikologi Perkembangan di Era Society 5.0 - Chaliza Anshary; Dira Anisah Ulfah Daulay; Homsani Nasution (Universitas Islam Negeri Sumatera Utara, 2026)
Digital content use among young children is rising rapidly in the Society 5.0 era, while its impact on expressive language remains debated. This article aims to synthesize evidence on the relationship between digital content, communication technology, and children’s expressive language development. The research is a library study using a narrative-integrative review approach that combines theoretical literature and empirical findings from the ERIC, Scopus, Google Scholar, and Garuda databases. Literature was purposively selected based on thematic relevance and analyzed using thematic analysis to build a coherent argument. The review is framed by three psychological lenses: developmental, social-emotional, and educational psychology. Findings show that passive content correlates negatively with expressive language through interaction displacement, whereas interactive, high-quality, adult-mediated media may support language development, with patterns differing by age group. The article recommends age-based content policies, strengthening ECCE teachers’ digital-pedagogical competencies, and integrating Islamic values.